Transmission Routes of COVID-19 Through Air, Water and Wastewater: A Systematic Review - Nematollah Jaafarzadeh; Sahand Jorfi; Zeinab Ghaedrahmat; Halime Almasi; Amir Zahedi (Hamadan University of Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this systematic review, five databases were searched (Scopus, PubMed-/Medline, Cochrane library, Embase, and Web of Science) for publications between 2019 to 12 February 2021. From 575 articles identified, seven papers were selected for inclusion. In the present paper, corona transmission routes from three environments of water, wastewater and air were considered. The most important transmission route of COVID-19 is through the air, which takes place from the following two routes: respiration and contact. Respiratory drops are caused by coughing and sneezing. Anyone who comes in close contact with someone having COVID-19 symptoms (sneezing, coughing, etc.) is potentially at risk for droplets. In this paper, corona transmission pathways from water, wastewater, and air in three environments were investigated. The results showed that the virus is transmitted through the air and its transmission through water and wastewater has not been proven. While the virus may survive in drinking water, there is no evidence that human coronavirus is present in surface and groundwater sources, or transmitted through contaminated drinking water. There is also no evidence of SARS-CoV-2 transmission through the sewage system, with or without wastewater treatment. Detection of this virus is very effective in determining the necessary and timely strategies to prevent further transmission of virus, and help to break the chain of COVID-19 transmission through water and wastewater.